Power System Modelling and Scripting - Milano, Federico; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Electric power systems are experiencing significant changes at the worldwide scale in order to become cleaner, smarter, and more reliable. This edited book examines a wide range of topics related to these changes, which are primarily caused by the introduction of information technologies, renewable energy penetration, digitalized equipment, new operational strategies, and so forth. The emphasis will be put on the modeling and control of smart grid systems. The book addresses research topics such as high efficiency transformers, wind turbines and generators, fuel cells, or high speed turbines and generators.
Power System Modelling -- Power System Architecture -- Power System Scripting -- Power System Analysis -- Power Flow Analysis -- Continuation Power Flow Analysis -- Optimal Power Flow Analysis -- Eigenvalue Analysis -- Time Domain Analysis -- Device Models -- Device Generalities -- Power Flow Devices -- Transmission Devices -- OPF Devices -- Faults and Protections -- Loads -- Alternate-Current Machines -- Synchronous Machine Regulators -- Direct-Current Devices -- AC/DC Devices -- FACTS Devices -- Wind Power Devices -- Spare Material and Concluding Remarks -- Data Formats -- Visualization Matters -- Challenges of Scripting for Power System Education.
Keywords: Engineering; Computer simulation; Computer science; Production of electric energy or power; Electric engineering; Engineering; Power Electronics, Electrical Machines and Networks; Energy Technology; Simulation and Modeling; Computational Intelligence; Computer Applications